HYDRA FOR WEB: WORDNET ONLINE EDITOR. - Rizov, Borislav; Dimitrova, Tsvetana (Bulgarian Language & Literature / Bulgarski Ezik i Literatura, 2017)
The paper presents the CRUD functions of the Hydra for Web system for work on lexical-semantic databases with relational structure similar to the structure of WordNet. It supports functionalities for editing of relational data, simultaneous access of multiple users, parallel data visualisation. Hydra for Web has been used for the development of the Bulgarian wordnet.